2021
DOI: 10.3390/ijerph18052229
|View full text |Cite
|
Sign up to set email alerts
|

Use of Health Services and Unmet Need among Adults of Russian, Somali, and Kurdish Origin in Finland

Abstract: Equal access to health care is one of the key policy priorities in many European societies. Previous findings suggest that there may be wide differences in the use of health services between people of migrant origin and the general population. We analyzed cross-sectional data from a random sample of persons of Russian (n = 692), Somali (n = 489), and Kurdish (n = 614) origin and the Health 2011 survey data (n = 1406) representing the general population in Finland. Having at least one outpatient visit to any me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Previous studies demonstrated that the lack of a common language between staff and patients is associated with decreased symptom reporting and fewer referrals to secondary and specialist care [ 41 ]. The lack of language skills to navigate the healthcare systems seems to be the prevalent barrier mentioned by researchers [ 61 , 62 , 63 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the lack of a common language between staff and patients is associated with decreased symptom reporting and fewer referrals to secondary and specialist care [ 41 ]. The lack of language skills to navigate the healthcare systems seems to be the prevalent barrier mentioned by researchers [ 61 , 62 , 63 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results with similar trends have been obtained from an earlier Finnish study. 35 As the models were adjusted for these sociodemographic variables, the observed differences in satisfaction with treatment were independent from them. Still, it is worth noting that there are significant differences in the providers of services used by different population groups, which should be taken into account when planning the services.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, immigrants had a higher risk of avoidable hospitalization (150). Referring to the site of healthcare, immigrants were found to be more likely to use healthcare services from public health facilities, while the general population also used private healthcare (151). However, IMs in some countries are more likely to visit private providers (33,37), traditional healers (37), and pharmacies (72) because of the lower costs associated with these healthcare service formats.…”
Section: Choice Of Types/sitesmentioning
confidence: 99%